Geothelphusa boreas, a new montane freshwater crab (Crustacea: Potamidae: Geothelphusa) from northeastern Taiwan, and the identity of G. hirsuta Tan & Liu, 1998 - Shy, Jhy-Yun; Shih, Hsi-Te; Mao, Jean-Jay (Zootaxa, 2021)
A new freshwater crab is described from the montane area in northeastern Taiwan based on morphological and molecular evidence. Geothelphusa boreas sp. nov., from the Fushan Botanical Garden situated around New Taipei City and Yilan County, is distinct from similar congeners by the structure of the male first gonopod and the proportions of the male thoracic sternites. In addition, after comparing the holotypes of G. takuan and G. hirsuta Tan & Liu, 1998, no substantial difference could be found. Molecular evidence from mitochondrial cytochrome oxidase subunit I also supports the recognition of the new species and the conspecificity of G. hirsuta with G. takuan.